Investigation on performance and mechanism of grafting activated waste leather powder modified asphalt. (21st February 2022) - Xia, Chengdong; Guo, Yanpeng; Lv, Songtao; Liu, Biao; Liu, TieJun; Zhao, Shungen; Liu, Yunhua
Highlights: The addition of Maleic anhydride grafted waste leather can greatly improve various properties of asphalt binder. The storage stability of modified asphalt is greatly enhanced after grafting waste leather with Maleic anhydride. Chemical reaction occurred between the grafting activated waste leather powder and base asphalt during modification process. Abstract: The objective of this study is to seek a methodology to recycle the waste leather in an efficient and eco-friendly way. In this study, modified asphalts samples containing 9% and 12% waste leather powder (WL) and Maleic anhydride grafted waste leather (MAH-WL), as well as base asphalt sample, were prepared. In addition, these tests of penetration, softening point, ductility, DSR, MSCR, fluorescence microscope, FTIR and SEM were applied to investigate the conventional physical performance, high-temperature rheological characteristic and storage stability of asphalt samples. The results indicated that under the same content of waste leather powder, grafting activation could reduce the penetration of asphalt and greatly improve the softening point and the ductility. Furthermore, the high-temperature rheological characteristic of MAH-WLMA was improved compared with base asphalt and WLMA. The storage stability of modified asphalt was also greatly enhanced after grafting Maleic anhydride to waste leather. The result of FTIR manifested that chemical reaction was occurred between the grafting activated waste leather powder and base asphalt, while the modification of waste leather without grafting was merely a physical process. Overall, using grafting activated waste leather as a bio-modifier of asphalt is feasible and promising, while some limits do exist. To comprehensively master the modification mechanism and apply MAH-WLMA to practical projects, further experiments need to be conducted. A range of performance of grafting activated waste leather asphalt mixture should also be investigated in the future.